Marshall, Marshallians and industrial economics - Raffaelli, Tiziano, 1950-; Nishizawa, Tamotsu, 1950-; Cook, Simon J. (Routledge studies in the history of economics., 2010)
This book€focuses on both Marshall and the Marshallian tradition, revisiting the 1920s and 1930s debates on business size, external economies, coordination and management costs€including contributions€from Roger€Backhouse and Richard Arena.